Best practices of local (Malaysian) automotive vendors [compact disc] - 367291 Hah, Dak Yen (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006